Estudo de transições de fase por Espectroscopia Raman em monocristais de L-asparagina monohidratada - Moreno, Antônio Jeferson de Deus (1996)
Polarized Raman spectra of cristais of 1-asparagine monohidrated over the range 3500-40 cm-1 were recorded since 10K untill the room temperature. The data obtained have been used to propose a general assignment of the vibrational fundamentals at room temperature on the base of temperature dependence of some modes and correlations with frequencies assigned in other aminoacids, principally the anidrous 1-asparagine which look like our compound. The coupling of the four zwitterions in the unit cell lead to 237 optical modes [60A + 59B1 + 59B2 + 59B3]. These data confirm that 1-asparagine monohydrated crystallize in an orthorhombic form with space group symmetry given by P212121 (D2). A great number of solid substances can be modeled as a dynamical system consisting of harmonic oscillators. However, some materials, as l-asparagine monohydrated and other hydrogen-bounded crystals, behave as anharmonic system. This leads to an important mechanism of broadening and shifting of the Raman lines. Temperature dependence polarized Raman studies show that although there are difference among Raman spectra below and above 160K, the selection rules are consistent with orthorhombic crystal structure in the temperature range 10-300K. There are changes in the numbers of external modes of B2 representation and in the internal modes of A representation. We also observed little changes in the slope of the temperature dependence of the Raman parameters. It was shown that the 1-asparagine monohidrated crystal axhibits various phase transitons with hidrostatic pressure. The first pressure-induced phase transition occur below 0.2 GPa and is accompanied by abrupt changes in the external and internal modes. The change of external modes of this region look like the observed changes at 160K in the temperature-dependence Raman spectra. The second phase transition occurs between 0,6 and 0,9 GPa and the third pressure induced phase transition is observed between 0,9 and 1,3 GPa. From the Raman data we observe the appearance of three hidrostatic pressureinduced phase transitions. Wowever, we expect tha further phase transitions can be observed for pressures above 2 GPa.